Desenvolvimento territorial : capital social e PROINF no território sertão ocidental de Sergipe - Nascimento, Patricia Oliveira do (2019)
Rural development has been the focus of discussions in academic circles during the last two decades. Public policymakers have started to analyze rural development from a perspective of "territorial politics", which aims to strengthen ‘place’ and promote a territorial style of development, focusing on economic, social, environmental, cultural and identity dimensions. The Support for Infrastructure Projects and Services in Rural Territories (Proinf) was established as a mechanism for economic inclusion, which contributes to the improvement of production, commercialization and training processes. The present study analyzes the actions and effects of Proinf in the Sergipe Western Rural Territory, specifically on the municipalities of Simão Dias and Poço Verde, from 2003 to 2016. The research is based on an empirical - analytical method, using qualitative and quantitative data. The methodological procedures consist of: a bibliographical review focusing on the topics Territory; Rural and territorial development; governance; social management and social capital. The field work is based on interviews that were conducted with 27 social actors involved in proinf, including representatives of the territorial collegiate (territorial advisors, state representatives of the collegiate, MST, CEFAC, ASCOB, EMDAGRO, IADH, representatives of the public power, proinf proponent (Poço Verde prefecture), and the association of beekeepers in the municipality of Poço Verde. Technical visits were made to three proinf projects (farmer training centers, honey collection points, agricultural marketing center, and questionnaires applied to 19 beekeeping beneficiaries of proinf. The survey data observed which projects were developed by the territorial collegiate and how they materialized in the territory. The dissertation concluded that social participation was an important element in the construction of this territorial policy. The PTC created mechanisms to foster social capital in the territories, strengthening the participation of civil society in the formulation and elaboration of projects that serve the rural environment, especially family agriculture, with the implementation of infrastructure, acquisition of equipment and training, to stimulate productive activities. It was verified that projects that did not meet territorial demands, and projects with low social return due to deficiencies in their elaboration, as well as a polarization of proinfs existed in two municipalities. But over the years the territory has strengthened, established a participatory collegiate, where projects were defined, demands discussed, and the model of social management strengthened by groups, resulting in more matured proinf proposals. In this context, it is important to emphasize the importance of promoting policies that develop the rural environment. After more than a decade of adopting these policies one can highlight significant advances in rural areas, even though there are several bottlenecks that need to be overcome. However, it is worth noting that the results are not short term, fostering social capital and development requires mechanisms and in this context the territory is very important element in this process for social constructions with a diversity of actors involved.